2021
DOI: 10.1016/j.molmet.2021.101391
|View full text |Cite
|
Sign up to set email alerts
|

Targeting the T-type calcium channel Cav3.2 in GABAergic arcuate nucleus neurons to treat obesity

Abstract: Objective Cav3.2, a T-type low voltage-activated calcium channel widely expressed throughout the central nervous system, plays a vital role in neuronal excitability and various physiological functions. However, the effects of Cav3.2 on energy homeostasis remain unclear. Here, we examined the role of Cav3.2 expressed by hypothalamic GABAergic neurons in the regulation of food intake and body weight in mice and explored the underlying mechanisms. Methods Male congenital C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 100 publications
1
3
0
1
Order By: Relevance
“…The same study also proposes that the effect of NAR on CCK is mediated by activating the TRPA1 channel, which allows the entry of extracellular calcium into the cell, since antagonists of this channel countered the effect of NAR on CCK. This is in agreement with the findings of Feng et al [ 102 ], who reported the blockade of ion channels in ARC neurons after NAR administration. Thus, NAR appears to exert some of its effects by modulating ion channel activity and intracellular calcium signaling ( Figure 3 ).…”
Section: The Hunger–satiety Pathwayssupporting
confidence: 94%
See 1 more Smart Citation
“…The same study also proposes that the effect of NAR on CCK is mediated by activating the TRPA1 channel, which allows the entry of extracellular calcium into the cell, since antagonists of this channel countered the effect of NAR on CCK. This is in agreement with the findings of Feng et al [ 102 ], who reported the blockade of ion channels in ARC neurons after NAR administration. Thus, NAR appears to exert some of its effects by modulating ion channel activity and intracellular calcium signaling ( Figure 3 ).…”
Section: The Hunger–satiety Pathwayssupporting
confidence: 94%
“…Most in vivo and in vitro studies describe a dose-dependent effect of NAR [ 19 , 42 , 87 ], still, its use has been studied in vivo at low doses (25 mg/kg body weight) [ 19 ] in a short period of time (2 days, intraperitoneal) [ 102 ] with positive results (see Table 1 ), which may support its use as a dietary supplement [ 65 ]. It is also important to consider that the documented effects regarding NAR are mainly preventive, protective and related to an improvement, but are not curative.…”
Section: The Hunger–satiety Pathwaysmentioning
confidence: 99%
“…As a main member of the T-type calcium channel, Cav3.2 channel has been reported to widely present in tissues throughout the body, including heart, brain, liver, lung, kidney and skin [12,29] . Numerous studies suggested that Cav3.2 channel play a crucial part in the development of various diseases, including myocardial infarction [13] , hypertension [14] , obesity [15] and diabetic neuropathy [16] . In addition, Cav3.2 inhibitors mibefradil and NNC 55-0396 were proven to improve hyperglycemia and hyperlipidemia in db/db mice [30] .…”
Section: Discussionmentioning
confidence: 99%
“…Cav3.2 channel is an important member of T-type calcium channel and involved in many cellular processes with different cell activities by regulating calcium in ux, including proliferation, migration, differentiation and apoptosis [11,12] . Numerous studies suggested that Cav3.2 channel play a crucial part in the development of various diseases, including myocardial infarction [13] , hypertension [14] , obesity [15] and diabetic neuropathy [16] . However, little is known on the function of Cav3.2 channel in the progression of NAFLD.…”
Section: Introductionmentioning
confidence: 99%
“…Sua principal fonte é o leite, seguido de vegetais e frutas. Baixos níveis séricos de cálcio no organismo têm sido associados a doenças como: osteoporose (Bae et al, 2022;Shen et al, 2021;Taylor & Elbadawy, 2006), osteomalácia (Taylor & Elbadawy, 2006), hipertensão (Potje et al, 2021), obesidade (Feng et al, 2021;Hastert et al, 2021), raquitismo (Mays & Brickley, 2022), enfraquecimento dos dentes e redução da capacidade de coagulação do sangue .…”
Section: Introdução Geralunclassified